Assessing Cumulative Musculoskeletal Strain in Automotive Mechanics: Insights from Real-World Occupational Analysis - Daneshmandi, Hadi; Sadeghian, Reyhane; Rahgoshay, Niloofar; Sartavi, Nahideh; Negahdari, Fardin; Golkari, Laleh (La Medicina del Lavoro, 2025)
Background: This cross-sectional study aims to assess cumulative loads affecting the lower back, shoulders, and distal upper extremities among automotive mechanics. Methods: The survey was conducted in automotive repair workshops in Shiraz, involving 157 independent mechanics selected through convenience sampling. Data were collected using a multiple-questionnaire including the Persian Cornell Musculoskeletal Discomfort Questionnaire (P-CMDQ), the Lifting Fatigue Failure Tool (LiFFT), the Shoulder Work Assessment Tool (SWAT), and the Distal Upper Extremity Tool (DUET). Descriptive statistics were used to assess musculoskeletal discomfort, and Partial correlation analyses, adjusted for age and Body Mass Index (BMI), examined the relationships between risk levels from LiFFT, SWAT, and DUET and discomfort reported in the P-CMDQ. Results: The results showed a high level of musculoskeletal discomfort, especially in the lower back, shoulders, and hands. Risk assessments indicated that the cumulative loads are in the high range for the lower back in 42.7% of cases, the shoulders in 40.8%, and the distal upper extremities in 36.3%. A strong correlation was observed between cumulative load on the lower back and perceived discomfort in this region (r = 0.730), whereas the correlations for the shoulders (r = 0.611) and distal upper extremities (r = 0.537) were moderate. Conclusions: The findings highlight the significant influence of workplace factors on the musculoskeletal health of automotive mechanics, emphasizing the importance of preventive measures and ergonomic solutions to enhance their health and productivity.